Upbringing for the community - the uncared function of education? - Kazimierz Czerwiński (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Communitarians - in a dispute with liberals - convince of a high importance of various communities for a constitution of the individual personality, especially its axiological horizon. However, the communities are able to take different forms, even the very oppressive one to individuals; Andrzej Szahaj lists the conditions of so-called "good community". Every community needs individuals who are involved in their existence and function as a group, but also who have specific attributes which are defined as virtues by the republican tradition. Certain educational activities, both closely associated with the teaching-learning process and the functioning of schools and universities as organizations, foster the formation of mentioned attributes. Primarily these educational activities are the various stimulative forms of human training such as: problem-based learning, project-based learning, team-based learning, discussion-based learning, and so forth.